Research orientation in Ayurveda educational institutions: Challenges and the way forward - Patwardhan, Kishor (J Ayurveda Integr Med, 2019)
This paper examines the scenario of research orientation in Ayurveda educational institutions of India. We demonstrate through the data obtained by searching the SCOPUS that the actual research output by these institutions is not very significant in terms of number of publications. While a lack of research expertise and infrastructure is one contributing factor to this status, a lack of questioning attitude is more crucial one. Mushrooming of new colleges, laxity in regulations, corruption, lack of atmosphere for ethical and quality research make the problem more complex. We show, with the help of SCOPUS Data, that the recent trend of establishing stand-alone institutions of Ayurveda may not help in invigorating research activities since the research contributions from such institutions have always been very poor. Instead, we suggest that existing stand-alone institutions of Ayurveda be merged with other established Central/State universities or other Medical colleges. The data demonstrates that the research output has been always significant when an institution has many experts working in different streams of science within, than when the institutions have only Ayurveda experts. We also take up the question of designing the clinical trials that are suitable for Ayurveda and propose an algorithm that may be considered for research in educational institutions, at least at doctoral level. We further enlist a set of recommendations that could potentially change the scenario. Evidence-informed policy making, inducting clinicians into the education system, making the curricula more attractive by including recent advances, introducing efficient faculty training programs, and rigorous implementation of the existing regulations - are some of the key recommendations we have made.